The use of GP IIb/Illa inhibitors during PCI: - Rawat, B; Bhatt, Y; Pande, R; Pandey, M; Poudyal, P; Verma, P; Agrawal, P; Chandra, P; Kasliwal, RR (Nepalese Heart Journal, 2004)
Glycoprotein (GP.IIb/llIa) inhibitors have shown the efficacy in reducing the Ischemic complications in patients undergoing PCI. Patients included in this study were those with history of unstable angina. The total number of patients who underwent PCI in our institute were 63, out of which 8 (12.69%) patients received GP.IIb/llla receptors antagonist (Reopro/Abciximab).The study group included 6 (75%) male patients and 2 (25%) female patients. Out of these, 6 (75%) patients had dyslipidemia, 4 (50%) patients had HTN, 3 (37.5%) had diabetes, 2 (25%) patients had past history of MI and 2 (25%) patients were smokers. The commonest nature of CAD was SVD in 4 (50%) patients and DVD in 4 (50%) patients. In 6 patients single stent was used and in 2 patients double stent was used. The size of the stents used were 3X18 mm in 6 and 3x14 mm in 2 patients .The procedural success was achieved in all patients. There was one in hospital death. The hospital stay was 2 days for all other patients and was uneventful.